Quality Function Deployment (QFD) application in developing mushroom-waste flour in Malaysia - Halim-Lim, Sarina Abdul; Barantaman, Roobini; Norhisham, Danial ‘Aizat; Di Renzo, Tiziana; Wan-Mohtar, Wan Abd Al Qadr Imad (Springer, 2025)
This study focused on valorisation nutrient-rich fruiting body wastes into value-added edible flour from mushroom waste which subsequently can be incorporated into production of atta flour chapattis as the main purpose of study. The present study uniquely combined QFD analysis revealed that mushroom taste (8.35), odour (8.35), and chapati texture (5) were the top consumers’ priorities. Next, a face-centered central composite design (CCD) was employed for the sensory analysis, to optimize MWF-infused chapatis formulations to achieve optimal consumer acceptance score. The particle size of 299.8 μm and MWF inclusion level at 6.1% yielded chapatis with a desirability value of 0.98, indicating high consumer appeal. The incorporation of MWF into the chapatis significantly influenced sensory attributes (p < 0.05) without impacting key physiochemical properties (moisture and ash content). Optimized MWF-infused chapatis formulation, exhibiting desirable flavour, odour, and texture, can be achieved using a particle size of 310 μm and a MWF inclusion at 6.8%, with a composite desirability value of 0.94. Therefore, this study demonstrated the potential for repurposing FBW of P. ostreatus into another valuable product with great consumer appeal. This study also provides a blueprint for improving the waste streams from various commercial mushroom farms, by converting them into highly accepted food products, thereby promoting sustainability in mushroom production.